Metagenomics for the development of new biocatalysts to advance lignocellulose saccharification for bioeconomic development. (1st November 2016) - Montella, Salvatore; Amore, Antonella; Faraco, Vincenza
Abstract: The world economy is moving toward the use of renewable and nonedible lignocellulosic biomasses as substitutes for fossil sources in order to decrease the environmental impact of manufacturing processes and overcome the conflict with food production. Enzymatic hydrolysis of the feedstock is a key technology for bio-based chemical production, and the identification of novel, less expensive and more efficient biocatalysts is one of the main challenges. As the genomic era has shown that only a few microorganisms can be cultured under standard laboratory conditions, the extraction and analysis of genetic material directly from environmental samples, termed metagenomics, is a promising way to overcome this bottleneck. Two screening methodologies can be used on metagenomic material: the function-driven approach of expression libraries and sequence-driven analysis based on gene homology. Both techniques have been shown to be useful for the discovery of novel biocatalysts for lignocellulose conversion, and they enabled identification of several (hemi)cellulases and accessory enzymes involved in (hemi)cellulose hydrolysis. This review summarizes the latest progress in metagenomics aimed at discovering new enzymes for lignocellulose saccharification.